Comparative transcriptome analysis of molecular mechanisms underlying adventitious root developments in Huangshan Bitter tea (Camellia gymnogyna Chang) under red light quality - Fu, Hao; Wei, Xu; Chen, Qian; Yong, Shunyuan; Liu, Qinjin; Dang, Jiangbo; Wu, Di; Liang, Guolu; Guo, Qigao (Frontiers in Plant Science, 2023)
As the formation of adventitious roots (AR) is an important component of in vitro regeneration of tea plants, the propagation and preservation of Huangshan Bitter tea (Camellia gymnogyna Chang) cuttings have been hindered due to its lower rooting rate. As light is a crucial environmental factor that affects AR formation, this study aimed to investigate the special role of red light (RL) in the formation of AR in Huangshan Bitter tea plants, which has not been well understood. Huangshan Bitter tea plants were induced with white light (control, WL) and red light (660 nm, RL) qualities 36 days after induced treatment (DAI) to investigate dynamic AR formation and development, anatomical observation, hormones content change, and weighted gene co-expression network analysis (WGCNA) of the transcriptome. Results showed that RL promoted the rooting rate and root characteristics compared to WL. Anatomical observations demonstrated that root primordium was induced earlier by RL at the 4 DAI. RL positively affected IAA, ZT and GA3 content and negatively influenced ABA from the 4 to 16 DAI. RNA-seq and analysis of differential expression genes (DEGs) exhibited extensive variation in gene expression profiles between RL and WL. Meanwhile, the results of WGCNA and correlation analysis identified three highly correlated modules and hub genes mainly participated in 'response to hormone', 'cellular glucan metabolic progress', and 'response to auxin'. Furthermore, the proportion of transcription factors (TFs) such as ethylene response factor (ERF), myeloblastosis (MYB), basic helix-loop-helix (bHLH), and WRKYGQK (WRKY) were the top four in DEGs. These results suggested that the AR-promoting potential of red light was due to complex hormone interactions in tea plants by regulating the expression of related genes. This study provided an important reference to shorten breeding cycles and accelerate superiority in tea plant propagation and preservation.